2015
DOI: 10.1097/ico.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Descemet-On Versus Descemet-Off Deep Anterior Lamellar Keratoplasty in Keratoconus Patients

Abstract: In conclusion, DALK procedures using the BB technique for keratoconus with DM-on or DM-off presented no significant differences regarding the visual outcomes or endothelial cell counts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…A recently conducted clinical trial comparing visual outcomes in patients undergoing DALK with and without removal of the donor DM and endothelium had results similar to ours (22) . We understand that the retrospective, non-comparative nature of this study has limitations.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…A recently conducted clinical trial comparing visual outcomes in patients undergoing DALK with and without removal of the donor DM and endothelium had results similar to ours (22) . We understand that the retrospective, non-comparative nature of this study has limitations.…”
Section: Discussionsupporting
confidence: 52%
“…Comparative studies found no significant differences after DALK in VA and contrast sensibility, irrespective of whether the donor endothelium was removed or left attached (20)(21)(22)(23) . The present study aimed to evaluate visual outcomes in patients with keratoconus undergoing DALK using full-thickness donor endothelial grafts.…”
Section: Introductionmentioning
confidence: 99%
“…Also, if an early detachment occurs (on the first or second postoperative day) due to a surgical perforation, which does not have a good response to rebubble, it is common for the button to remain transparent. In addition, there are studies that show no significant advantage in ­removing the DM from the donor (11, 12).…”
Section: Discussionmentioning
confidence: 99%
“…It is with great interest that we read the article published by Prazeres et al 1 The authors prospectively compared the outcome of Descemet's membrane-on with Descemet's membrane-off deep anterior lamellar keratoplasty in patients with keratoconus.…”
Section: To the Editormentioning
confidence: 99%